Pengaruh Beban Kerja dan Kompetensi terhadap Stres Kerja : Studi di Puskesmas Se-Kota Banjar (International Forum of Researchers and Lecturers, 2023)
The problems faced in this study include (1) How does workload affect work stress in Puskesmas in Banjar City? (2) What is the effect of competence on work stress in Puskesmas in Banjar City? (3) How does workload and competence affect work stress in Puskesmas in Banjar City? This study aims to study, know, and analyze (1) The effect of workload on work stress in Puskesmas in Banjar City? (2) The effect of competence on work stress in Puskesmas in Banjar City? (3) The effect of workload and competence on work stress in Puskesmas throughout Banjar City. The method used in this study is an explanatory survey, while the data analysis technique is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis with Multiple Regression. The results of the study inform that (1) The workload in the Banjar City Health Center is very high. With the highest score on the physical demand indicator and the lowest score on the task demand indicator. Workload has a positive effect on work stress in Puskesmas throughout Banjar City. This means that if the workload is increased, then the work stress at the Banjar City Health Center will also increase. (2) The competence in the Banjar City Health Center is very high. With the highest score on the individual characteristics indicator and the lowest score on the knowledge indicator. Competence has a positive effect on work stress in Puskesmas throughout Banjar City. This means that if Competence is improved, then work stress at the Banjar City Health Center will also increase. (3) Work stress in Puskesmas in Banjar City is high. With the highest score on the anxiety indicator and the lowest score on the indicator cannot relax. Workload and competence have a positive effect on work stress in Banjar City Health Centers. This means that if the workload and competence are increased, then the work stress at the Banjar City Health Center will also increase.